Pengaruh Belanja Modal, Intergovernmental Revenue, Leverage, Size dan Pendapatan Alsi Daerah Terhadap Kinerja Keuangan Pemerintah Daerah Kota dan Kabupaten di Pulau Jawa Tahun 2014 - Novyandra, Rokhim; , Drs. Atwal Arifin, Ak.,M.Si (2016)
The emergence of MPR Decree No. XV/MPR/1998 on "Implementation of Autonomous Regions, Distribution and Utilization of National Resources Fair Indonesia" has responsibility for local government that is big enough. Responsibility is one of them can be evidenced by the performance of pemerinrah area. Performance is the picture of the achievement of the vision, mission, and goals of an organization. This research was conducted in order to obtain empirical evidence related to the effect of capital expenditures, the intergovernmental revenue, size, leverage and local revenues on the financial performance of local governments. The population of this research is all local government district / city island of Java in fiscal year 2014. The total sample of this research are 43 local government district / city are taken by using purposive sampling. Data were analyzed using multiple linear regression analysis results showed that capital spending and intergovernmental revenue significantly influence the financial performance of local government districts / cities in Java. As for size, leverage and local revenues do not affect the financial performance of local government districts / cities in Java.